'How long does it take?' A mixed-method evaluation of computer-related work in GP consultations. Issue 4 (1st October 2015) - Hayward, James; Buckingham, Susan; Thomson, Fionagh; Milne, Heather; Sheikh, Aziz; Fernando, Bernard; Cresswell, Kathrin; Williams, Robin; Pinnock, Hilary
Abstract : Background: Systematic reviews have suggested that time spent on computerrelated tasks increases consultation length. However, these reviews pre-date the current ubiquitous use of computers in U.K. general practice. Objective: As part of a U.K. national study of the influence of information technology (IT) on the interaction between patients and healthcare professionals during consultations, we explored how IT functions affected time allocation and styles of computer use during general practitioner (GP) consultations. Methods: We drew on multichannel video recording of consultations and measured consultation phases and the duration of computer-related tasks. We related measures of actual time to GP's interpretation of computer use elicited in qualitative interviews. Results: Our sample included recordings of 112 consultations from 6 GPs in three practices. The computer was used for about one-third of the greater consultation. However, its use was concentrated pre- and post- the patient consultation. The workflow of consultation was exemplified through six computer use cases. Most functionality was accepted and accommodated within the consultation, though disruptive and time-consuming tasks were generally delegated to administrative staff. Recognised styles of computer use (minimal, block and conversational) were apparent, but applied very flexibly by GPs according to the nature of the consultation. Conclusions: In contrast to earlier reports, contemporary computer use does not appear to have lengthened consultations. GPs adopted different styles of computer use in different consultations, challenging classifications that seek to stereotype GP computer use. Designing systems that support this versatility require an understanding of the fluid application of computer use within consultation structure. What is already known: Although computers have been used in U.K. general practice consultations for four decades, there are on-going concerns about the amount of time new computer functions may take. General practitioners (GPs) adopt different styles of computer use during patient consultations. What this paper adds: This study found no evidence that computer use increases the length of consultation. The electronic health record is now the accepted norm in U.K. primary care, and in general, GPs do not express concerns about the time allocated to undertaking computer-related tasks within the consultation. Implications for clinical practice: Despite some preferences in how they used the computer within the consultation, all the GPs readily adapted their style to suit the individual consultation. Understanding of the skilful versatile strategies employed by GPs may be a useful design resource and inform clinical training. Computer designers need to address the tension between ordered computer function and the fluid demands of a clinical consultation.